Middle ear neuroendocrine tumor with multiple brain metastases: a case report and literature review - Sun, Yesheng; Zhang, Ying; Cai, Dongpeng; Zhang, Wei; Yang, Zhiqian (Frontiers in Oncology, 2024)
Middle ear neuroendocrine tumor (MeNET) is a low-grade tumor with rare recurrence or metastasis. Here, we describe the case of a 29-year-old man who suffered from MeNET that recurred 3 times over 10 years and eventually metastasized to the brain. The patient was treated with surgical resection, radiotherapy, and chemotherapy. However, the tumor was not entirely removed as the brain metastatic tumor adhered tightly to the brainstem. Due to tumor rupture and bleeding after multiple brain tumor removal, profound coma developed. Finally, the patient died 10 months after the last surgery. To our knowledge, this is the first report of a MeNET case with multiple brain metastases. Characteristics of the present case indicate that CK, SYN, increased Ki67 index, and ATRX may be potential biomarkers of invasive MeNET. The survival of patients with brain metastatic MeNET may be extended by surgical resection, radiotherapy, and chemotherapy. Close follow-up of distinctive metastases and biomarkers related to recurrence is also suggested.